2016
DOI: 10.1002/2016ja022950
|View full text |Cite
|
Sign up to set email alerts
|

A statistical analysis of equatorial plasma bubble structures based on an all‐sky airglow imager network in China

Abstract: This paper investigates the statistical features of equatorial plasma bubbles (EPBs) using airglow images from 2012 to 2014 from a ground‐based network of four imagers in the equatorial region of China. It is found that (1) EPBs mainly occur during 21:00–00:00 local time (LT) in equinoxes. There is an asymmetry in occurrence rates between March (June) and September equinoxes (December solstices). (2) Most EPBs occur in groups of two to six depletions. The distance between adjacent EPB depletions is ~100–700 km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 74 publications
9
42
0
Order By: Relevance
“…This shape has previously been suggested to be caused by latitudinal variation of zonal plasma drift and/or the polarization electric field inside the EPBs. During this study event, estimation of the eastward drift velocity of 80-120 m/s near the magnetic equator can be achieved through comparing the differences (∼2-3 • ) of the central location of the Dark Streaks #1 between Figures 2a and 2d, which is consistent with the zonal drift velocities measured by ionosondes in Figures 4e and 4f and previous experimental/modeling studies of EPBs zonal drift velocities (Chapagain et al, 2012;Gurav et al, 2018;Huba et al, 2009;Sun et al, 2016). This vertical electric field further drives an eastward E × B drift of the F region plasma with nearly similar velocities as the neutral wind.…”
Section: Discussionsupporting
confidence: 83%
“…This shape has previously been suggested to be caused by latitudinal variation of zonal plasma drift and/or the polarization electric field inside the EPBs. During this study event, estimation of the eastward drift velocity of 80-120 m/s near the magnetic equator can be achieved through comparing the differences (∼2-3 • ) of the central location of the Dark Streaks #1 between Figures 2a and 2d, which is consistent with the zonal drift velocities measured by ionosondes in Figures 4e and 4f and previous experimental/modeling studies of EPBs zonal drift velocities (Chapagain et al, 2012;Gurav et al, 2018;Huba et al, 2009;Sun et al, 2016). This vertical electric field further drives an eastward E × B drift of the F region plasma with nearly similar velocities as the neutral wind.…”
Section: Discussionsupporting
confidence: 83%
“…The different aspects of EPBs have been studied by many researchers such as occurrence characteristics (e.g., Candido et al, ; Makela et al, ; Sahai et al, ; Sharma, Gurav, et al, ; Sharma et al, ; Sun et al, ), morphology and evolution (e.g., Aggson et al, ; Huba et al, ; Narayanan et al, ; Wu et al, ), statistical features of EPBs (e.g., Narayanan et al, ; Sinha & Raizada, ; Sun et al, ), and zonal drift velocity (e.g., Abalde et al, ; Immel et al, ; Mukherjee & Shetti, ; Nade et al, ; Paulino et al, ; Pimenta et al, ; Taori et al, ; Yao & Makela, ). However, there are different techniques to monitor and study the evolution and characteristics of these large‐scale structures (EPBs) such as incoherent scatter radar (e.g., Fejer et al, ), VHF spaced receiver system (e.g., Bhattacharyya et al, ; Sharma, Chavan, et al, ; Sharma et al, ), Fabry‐Pérot interferometer (e.g., Sahai et al, ), GPS (e.g., Haase et al, ; Ji et al, ; Nade et al, ), and ASI (e.g., Fagundes et al, ; Ghodpage et al, ; Kishore & Mukherjee, ; Nade et al, ; Pimenta, Bittencourt, et al, ; Sobral et al, ; Taori & Sindhya, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al () investigated the statistical features of EPBs using airglow images from 2012 to 2014, which lies in the increasing phase of 24th solar cycle from a ground‐based network of four ASIs in the equatorial region of China. They calculated zonal drift for the period of March–April 2012 to 2014 and found that EPBs usually have a maximum drift near 100 m/s at 21:00–22:00 LT in 9.5° ± 1.5° geomagnetic latitude and then decrease to 50–70 m/s toward dawn period.…”
Section: Introductionmentioning
confidence: 99%
“…Note that a previous statistical study done by Sun et al [] indicates that the EPBs in the almost same region usually extended poleward to attain the maximum magnetic latitude at about 22:00–00:00 LT and then quickly retreated back toward the equator. However, the EPB airglow depletions shown in Figure had no obvious equatorward motion after they became fossil bubbles.…”
Section: Resultsmentioning
confidence: 80%
“…The ASAIs of the same type have been previously used to study mesospheric gravity waves [ Li et al ., , , ; Xu et al ., ] and thermospheric medium‐scale traveling ionospheric disturbances (MSTIDs) [ Sun et al ., ]. A statistical study on the EPB airglow structures was also done by Sun et al [] in the almost same equatorial region of China. With a Mamiya 24 mm/f4.0 fish‐eye lens and a 180° FOV, this type of imager has a CCD detector consisted of 1024 × 1024 pixels with a pixel depth of 16 bits.…”
Section: Observationmentioning
confidence: 99%